Poverty and Individual Responsibility - Paolo Giovanni Piacquadio (Center for Economic Studies and ifo Institute (CESifo), 2020)
Poverty-reducing policies ought to prioritize the "deserving" poor, that is, those who do all that can be reasonably expected from them in their circumstances, but fail to achieve a minimum standard of living. To inform such policies, one needs a theory of justice accommodating norms of individual responsibility. I propose and axiomatically characterize a family of poverty indices that address these issues. Formally, poverty is measured by the sum of specific indices of individual deprivation which (i) keep individuals accountable for their choices, (ii) compare individuals based on the set of attainments they are deprived of, and (iii) prioritize the most deprived individuals. I illustrate the results with Norwegian register data. Among single males, about a third of the income-poor ones are "undeserving," because (based on the estimates) they are unwilling to accept a job that brings them out of poverty.
Keywords: D63; I30; 330; multidimensional poverty; responsibility; fairness